A Survey of the Role of Community Pharmacists in Dhaka city, Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
Community pharmacists play a vital role in improving medication safety and better healthcare facility to the community. Unfortunately, the field of community pharmacy in Bangladesh is still to be developed and there is scarcity of data regarding current role of community pharmacists in Bangladesh. The present study was conducted to find out the role of community pharmacists in Bangladesh. For the study purpose, we visited 42 retail pharmacies in Banani, Khilkhet and Uttra areas of Dhaka city and interviewed the community pharmacists working there. We found that there were total 50 community pharmacists in 42 retail pharmacy and also observed that most of the pharmacists (64%) worked alone. Interestingly, we didnt find a single A-grade pharmacist working as community pharmacist. B-grade pharmacists who completed a 3 year diploma in pharmacy were only 4 in number and 92% of them were C-grade pharmacists with 3-4 months training. The average age of the participants was 29.6 ± 1.2 years. The average length of service for the community pharmacists was 7.6 ± 1.3 years. The top issues that patients consulted with the pharmacists were on medication use (76%), which physician they should visit (54%) and therapy (26%). There was not a significant effect of work experience of community pharmacists on their attitudes toward community-based clinical services. In this study, we observed that 95% community pharmacies provide blood pressure measurement facility, 90% provide diabetes screening, 76% provide dressing services, and only 47% provide nebulization. No community pharmacist was found to be involved with adverse drug reaction reporting. In conclusion, we recommend that the government and the pharmacy regulatory authority should take sufficient initiatives to develop the community pharmacy sector in Bangladesh for the welfare of mankind.Bangladesh Pharmaceutical Journal 18(2): 137-141, 2015